2019
DOI: 10.1073/pnas.1901562116
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils promote tumor resistance to radiation therapy

Abstract: Nearly two-thirds of cancer patients are treated with radiation therapy (RT), often with the intent to achieve complete and permanent tumor regression (local control). RT is the primary treatment modality used to achieve local control for many malignancies, including locally advanced cervical cancer, head and neck cancer, and lung cancer. The addition of concurrent platinum-based radiosensitizing chemotherapy improves local control and patient survival. Enhanced outcomes with concurrent chemoradiotherapy may r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
93
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(113 citation statements)
references
References 63 publications
(62 reference statements)
7
93
1
1
Order By: Relevance
“…Myeloid cells (i.e. type I and type II macrophages, M1 and M2 respectively) were the most abundant immune cell population ( Figure 4E), consistent with previous reports of autochthonous KP sarcomas 44 .…”
Section: Acute Digoxin Treatment Remodels the Immune Compartment Of Tsupporting
confidence: 91%
See 3 more Smart Citations
“…Myeloid cells (i.e. type I and type II macrophages, M1 and M2 respectively) were the most abundant immune cell population ( Figure 4E), consistent with previous reports of autochthonous KP sarcomas 44 .…”
Section: Acute Digoxin Treatment Remodels the Immune Compartment Of Tsupporting
confidence: 91%
“…It will be interesting in future studies to determine the functional consequences of these variations in metabolic reprogramming between immune cell populations, especially upon consideration of previous studies reporting consequences of digoxin on immune cell activity in various noncancerous settings 70,71 . Additional studies of these interactions could illuminate possible synergistic mechanisms that may elicit enhanced clinical efficacy of digoxin when combined with targeted immune therapies as has been found with other compounds 44,72,73 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, a study communicated very recently by Wisdom et al has indicated that TANs may also attenuate the efficacy of traditional anti-cancer therapies such as radiation therapy [42]. In this retrospective, single-centre study conducted during the period 2006-2017, the authors investigated associations between pre-treatment circulating neutrophil counts and responsiveness to definitive chemo-radiation in patients (n = 278) with cervical cancer [42], a malignancy in which the TAN count had previously been reported to be an independent prognostic factor for short recurrence-free survival [43]. Wisdom et al observed that lower pre-treatment circulating neutrophil counts were correlated with enhanced efficacy of chemo-radiation therapy (higher rates of local control, metastasis-free survival and overall survival) [42].…”
Section: Recruitment and Exploitation Of Neutrophils By Tumorsmentioning
confidence: 99%